A New Species of Phyllanthus (Phyllanthaceae) from Northeastern Brazil - Santos, Diego; Sousa, Luana Mateus De; Torres, Alícia Marques; Silva, Marcos José Da; Loiola, Maria Iracema Bezerra (Phytotaxa, 2025)
Phyllanthus catingicola, a new species endemic to Northeastern Brazil, is here described and illustrated based on morphological data. It is known so far in the state of Ceará and is morphologically similar to P. hyssopifolioides in having a stem with non-phyllanthoid branching, secondary branches flat and discreetly winged, leaves present on the main stem and secondary branches, staminate disk with surface smooth and pistillate flowers 6-merous. However, they differ by a set of characters related to the shape of the main stem, number and shape of the staminate sepals, and the shape of the pistillate disk and stigma. We provide photographs of the species in the field, its conservation status, mapped distribution, systematic positioning, and a comparative table to differentiate it from other similar species belonging to Phyllanthus sect. Loxopodium.